Efektifitas aplikasi Beauveria bassiana sebagai upaya pengendalian wereng batang coklat dan walang sangit pada tanaman padi di Desa Campursari Kecamatan Bulu Kabupaten Temanggung - Tri Purwaningsih; Budi Adi Kristanto; Karno Karno (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
Beauveria bassiana is one of the pathogens that can be used as an environmentally friendly bio pesticide, as it does not produce harmful residues and does not cause pest resistance. This research was conducted in the village of Campursari village, District of Bulu, Temanggung Regency. The purpose of this research was assess the effectiveness of Beauveria bassiana application in order to suppress the population of brown planthopper and adult rice bug in rice plants and to find out rice plants production. The research used factorial randomized design which consists of two treatments. The first treatment was the application of Beauveria bassiana with controlled doses by 0, 100, 150 and 200 g/14 l. The second treatment was the application interval between 7, 10, and 14 days. The parameters observed were brown planthopper populations, adult rice bug population, plant height, number of tillers and grain production. The results showed that application with doses of 200 g/14 l and 7 day interval application was effective to suppress population of brown planthopper and adult rice bug and also saved grain production by 1,20 kg to 7,02 kg/m2 depending on application dosage. Keywords : planthopper, adult rice bug, Beauveria, doses, application interval